2017
DOI: 10.1128/aem.03005-16
|View full text |Cite|
|
Sign up to set email alerts
|

A Plant Bacterial Pathogen Manipulates Its Insect Vector's Energy Metabolism

Abstract: Insect-transmitted plant-pathogenic bacteria may alter their vectors' fitness, survival, behavior, and metabolism. Because these pathogens interact with their vectors on the cellular and organismal levels, potential changes at the biochemical level might occur. "Candidatus Liberibacter asiaticus" (CLas) is transmitted in a persistent, circulative, and propagative manner. The genome of CLas revealed the presence of an ATP translocase that mediates the uptake of ATP and other nucleotides from medium to achieve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 46 publications
(54 reference statements)
6
51
1
Order By: Relevance
“…As expected, "Ca. Liberibacter asiaticus" infection of psyllids and citrus raises the levels of host glycolysis, TCA cycle metabolites, respiration rates (39), and ATP content (45,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, "Ca. Liberibacter asiaticus" infection of psyllids and citrus raises the levels of host glycolysis, TCA cycle metabolites, respiration rates (39), and ATP content (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli was grown in Luria-Bertani medium at 37°C. L. crescens and X. albilineans were cultured in BM7 medium (11) and Modified Wilbrink's medium (45), respectively, at 28°C. Genomic DNA from L. crescens and X. albilineans cells was extracted using the GenElute Bacterial Genomic DNA kit (Sigma-Aldrich, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with a recent study suggesting that in the psyllid Las alters the host environment to enhance nutrient availability and increase ATP levels. 77 This leads to the intriguing possibility that Las may directly or indirectly increase the ATP level in plant tissues as well for subsequent importation through its translocase directly from its host. Thus, information provided in this study has revealed molecular and physiological mechanisms involved in the host response to HLB and potential new targets for control strategies.…”
mentioning
confidence: 99%
“…DNA from adult psyllids (5 biologic replicates of 5 insects/replicate) was extracted using potassium acetate buffer as described by Killiny et al . The extracted DNA was quantified using a Nano‐Drop 2000 spectrophotometer (Thermo Scientific) and adjusted to 100 ng μL −1 .…”
Section: Methodsmentioning
confidence: 99%
“…DNA from adult psyllids (5 biologic replicates of 5 insects/ replicate) was extracted using potassium acetate buffer as described by Killiny et al 57 The extracted DNA was quantified using a Nano-Drop 2000 spectrophotometer (Thermo Scientific) and adjusted to 100 ng μL −1 . Extracted DNA was used for RT-qPCR amplification using 16S rRNA primers HLBasf and HLBr, the probe HLBp, TaqMan PCR master mix, SYBR green PCR master mix, and the protocol described by Li et al 58 and Zhao et al 59 qPCR assay was performed in a 96-well plate using an ABI 7500 RT-qPCR system, and supplies were from Applied Biosystems (Foster City, CA, USA) as described by Killiny et al 57…”
Section: Bacterial Cell Quantification By Realtime Pcr For Clasmentioning
confidence: 99%